β-Adrenergic Receptor-Dependent Alterations in Murine Cardiac Transcript Expression Are Differentially Regulated by Gefitinib In Vivo - Talarico, Jennifer A. (Public Library of Science, 2014)

(untitled)
β-adrenergic receptor (βAR)-mediated transactivation of epidermal growth factor receptor (EGFR) has been shown to promote cardioprotection in a mouse model of heart failure and we recently showed that this mechanism leads to enhanced cell survival in part via regulation of apoptotic transcript expression in isolated primary rat neonatal cardiomyocytes. Thus, we hypothesized that this process could regulate cardiac transcript expression in vivo. To comprehensively assess cardiac transcript alterations in response to acute βAR-dependent EGFR transactivation, we performed whole transcriptome analysis of hearts from C57BL/6 mice given i.p. injections of the βAR agonist isoproterenol in the presence or absence of the EGFR antagonist gefitinib for 1 hour. Total cardiac RNA from each treatment group underwent transcriptome analysis, revealing a substantial number of transcripts regulated by each treatment. Gefitinib alone significantly altered the expression of 405 transcripts, while isoproterenol either alone or in conjunction with gefitinib significantly altered 493 and 698 distinct transcripts, respectively. Further statistical analysis was performed, confirming 473 transcripts whose regulation by isoproterenol were significantly altered by gefitinib (isoproterenol-induced up/downregulation antagonized/promoted by gefinitib), including several known to be involved in the regulation of numerous processes including cell death and survival. Thus, βAR-dependent regulation of cardiac transcript expression in vivo can be modulated by the EGFR antagonist gefitinib.